Interactions between Leishmania braziliensis and Macrophages Are Dependent on the Cytoskeleton and Myosin Va - Elisama Azevedo; Leandro Teixeira Oliveira; Ana Karina Castro Lima; Rodrigo Terra; Patrícia Maria Lourenço Dutra; Verônica P. Salerno (Journal of Parasitology Research)
Leishmaniasis is a neglected tropical disease with no effective vaccines. Actin, microtubules and the actin-based molecular motor myosin Va were investigated for their involvement in Leishmania braziliensis macrophage interactions. Results showed a decrease in the association index when macrophages were without F-actin or microtubules regardless of the activation state of the macrophage. In the absence of F-actin, the production of NO in non-activated cells increased, while in activated cells, the production of NO was reduced independent of parasites. The opposite effect of an increased NO production was observed in the absence of microtubules. In activated cells, the loss of cytoskeletal components inhibited the release of IL-10 during parasite interactions. The production of IL-10 also decreased in the absence of actin or microtubules in non-activated macrophages. Only the disruption of actin altered the production of TNF-α in activated macrophages. The expression of myosin Va tail resulted in an acute decrease in the association index between transfected macrophages and L. braziliensis promastigotes. These data reveal the importance of F-actin, microtubules, and myosin-Va suggesting that modulation of the cytoskeleton may be a mechanism used by L. braziliensis to overcome the natural responses of macrophages to establish infections.